Pol??tica educacional de forma????o de jovens e adultos: o processo de implementa????o do PROEJA no IFPI campus Picos entre os anos de 2007 e 2017 - Silva, Fernanda Pereira da (2018)
This research has as object of study the National Program of Integration of the Professional Education with the Basic Education, in the Mode of Education of Young and Adults (PROEJA), and its implementation in the IFPI, campus Picos. The PROEJA constitutes an educational policy directed to the care of young people and adults. Through the proposal of the integrated curriculum, it articulates Basic Education, Professional Education and Education of Youths and Adults, in the perspective of expanding schooling. The objective was to understand, from the perception of managers and teachers, the context and difficulties encountered in the implementation process of the Program between 2007 and 2017. The research, with a qualitative approach, used different methodological procedures, such as bibliographic review of authors that base the debate on EJA, integrated curriculum and Professional Education; reading and analysis of documents and legislation that guides PROEJA; semi-structured interviews with managers and teachers, systematized based on Content Analysis. The data found allow us to infer difficulties in the process of implementing PROEJA in aspects such as a training of professionals, an understanding of the specificities of the students, as well as the knowledge of the effectiveness of the integrated curriculum and the insertion of students in the institution. Thus, although the IFPI, Campus Picos has been guaranteeing the offer PROEJA since the year 2007 and the presence of the Program on campus is seen positively by the managers and teachers, many aspects of its effectiveness are fragile and need reorientation so that possible.